The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1063/5.0039131
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and relieving the thermal issues caused by fabrication details of a deuterium cryogenic target

Abstract: In inertial confinement fusion experiments, fuel quality is determined mainly by the thermal environment of the capsule in the layering procedure. Owing to the absence of a radial thermal gradient, formed deuterium–deuterium (DD) ice shells in the capsule are thermally instable. To obtain a solid DD layer with good quality and long lifetime, stringent demands must be placed on the thermal performance of cryogenic targets. In DD cryogenic target preparation, two issues arise, even after the capsule’s temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The capsules are further cooled below the deuterium solidification temperature when the amounts of the liquid fuel inside the capsules meet the design requirements. Following specific procedures of temperature control [21,22], it is found that a uniform D-ice layer can survive for a few minutes inside the capsule. We repeated the procedures of D-ice layering fourteen times for a single target, and by characterizing the ice layer quality with phase contrast imaging (figure 2), we found that there was a 72% chance that the amplitude of mode 1 was less than 2.8 µm, and the RMS of the power spectrum in modes 2-100 was 2.2 µm in average.…”
Section: Methodsmentioning
confidence: 99%
“…The capsules are further cooled below the deuterium solidification temperature when the amounts of the liquid fuel inside the capsules meet the design requirements. Following specific procedures of temperature control [21,22], it is found that a uniform D-ice layer can survive for a few minutes inside the capsule. We repeated the procedures of D-ice layering fourteen times for a single target, and by characterizing the ice layer quality with phase contrast imaging (figure 2), we found that there was a 72% chance that the amplitude of mode 1 was less than 2.8 µm, and the RMS of the power spectrum in modes 2-100 was 2.2 µm in average.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we present our latest progress on the fabrication and characterization of MgB 2 spherical shells. As the diameter of the capsule in ICF may vary from about 1 to 2 mm depending on the specific design and facility [19,27], we have expanded our shell fabrication on 2 mm diameter Si 3 N 4 spheres to include that on 1 mm diameter spheres as well. For both diameters (d = 2 mm and 1 mm), the T c of the MgB 2 spherical shells has been improved to the bulk value of 39 K. Electrical transport and magnetization measurements under magnetic fields have been carried out to determine the current-carrying capability as well as various characteristic fields that define the superconducting phase diagram of the spherical shells.…”
Section: Introductionmentioning
confidence: 99%